Investigation of salivary biomarkers as indicators of skeletal and dental maturity in children. (6th April 2022) - Tsagkari, Eirini; Deda, Olga; Krokos, Adamantios; Gika, Helen; Papadopoulos, Moschos A.; Chatzigianni, Athina
Abstract: Objective: Estimation of patient's skeletal maturity in orthodontics is essential for the diagnosis and treatment planning. The aim of the study was to investigate the potential use of metabolic fingerprint of saliva for bone growth and tooth development estimation. Materials and Methods: Saliva samples from 54 young patients were analysed by an untargeted gas chromatography‐mass spectrometry metabolomics‐based method. The skeletal maturity was calculated with the cervical vertebrae maturation method, and the dental age was estimated with the Demirjian method. Multivariate analysis and univariate analysis were performed to investigate differences within skeletal, dental and chronological age groups. Results: Metabolomic analysis identified 61 endogenous compounds. Mannose, glucose, glycerol, glyceric acid and pyroglutamic acid levels differentiated significantly with skeletal age ( P  = .02 to .043), while mannose, lactic acid, glycolic acid, proline, norleucine, 3‐aminoisobutyric acid, threonine, cadaverine and hydrocinnamic acid levels differed within the dental age groups ( P  = .018 to .04); according to the chronological age, only the levels of mannose and 3‐hydroxyphenylacetic acid showed variation ( P  = .029 and .048). The principal component analysis did not manage to highlight differences between the groups of the studied parameters. Conclusion: Differentiated levels of mannose, glucose, glycerol, glyceric acid and pyroglutamic acid related to skeletal maturation were identified. According to dental development, the levels of mannose, lactic acid, glycolic acid, proline, norleucine, 3‐aminoisobutyric acid, threonine, cadaverine and hydrocinnamic acid differed within the groups, while regarding chronological age, only the levels of mannose and 3‐hydroxyphenylacetic acid showed variations. Further studies are required to prove their relation to skeletal and dental development pathway by applying complementary analytical techniques to wider cover the metabolome.